PENGEMBANGAN MEDIA BERBASIS GOOGLE CLASSROOM PADA MATA PELAJARAN EKONOMI - Pratama Irfaan H; Suarman Suarman; Hardisem Herdisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study has the objectives, among others 1) To produce media based on Google Classroom in economic subjects 2) To determine the feasibility of media based on the assessment of media experts and material experts on Google Classroom media design in economic subjects. Then the research method used ie R & D by using part of the model ADDIE (Analysis, Design, and Development). To determine the feasibility of this research, validation was carried out by media experts and material experts with the end result of the media being categorized as very good and worthy of being tested in the field. This media development is only intended for high school economics subjects. This research is still not perfect, so it is hoped that further research can be perfected up to the implementation and evaluation stages.Key Words: Media, Developing, Google Classroom